Influence of phase coarsening and filler agglomeration on electrical and rheological properties of MWNTs-filled PP/PMMA composites under annealing. (19th November 2015) - Chen, Yian; Yang, Qi; Huang, Yajiang; Liao, Xia; Niu, Yanhua
Abstract: The morphology, rheological and conductive behaviors of polypropylene (PP)/poly(methyl methacrylate) (PMMA)/multi-walled carbon nanotubes (MWNTs) composites induced by annealing were studied. There was a double percolated structure that MWNTs particles were selectively localized at the interface in the PP/PMMA/MWNTs composites. The electrical percolation of the double percolated structure was 0.48 wt%. Annealing induced MWNTs secondary agglomeration and coarsening. The two processes both reduced the distance between MWNTs. Thus the electrical percolation threshold of the PP/PMMA/MWNTs composites after annealing can be as low as 0.09 wt%. The rheological measurements indicated that a special rheological percolation (named as morphology rheological percolation) which closely relate to the morphological transition was very differ from the rheological percolation which closely relate to the formation of the rheological network. The networking of nanoparticles made a more significant contribution to the evolution of storage modulus than phase coarsening. Graphical abstract: Highlights: The electrical percolation threshold of the composites after annealing can be as low as 0.09 wt%. The networking of nanoparticles made a more significant contribution to the evolution of storage modulus than phase coarsening.